DETERMINING THE ETHICAL PROBLEMS EXPERIENCED BY NURSING STUDENTS IN CLINICAL EDUCATİON - RIZALAR, Selda; AKTAY, Elif Beyza; AKÇAOVA, Şevval (Göbeklitepe Medical Science Journal, 2025)
This study was conducted as descriptive and cross-sectional to determine the ethical problems experienced by nursing students in clinic education, with 350students of a foundation university in Istanbul. Data were collected using an information form and a Scale of Ethical Problems in clinical education. Data were evaluated using the SPSS 21 program using number, percentage, mean, Mann-WhitneyU and Kruskal-Wallis tests.It was determined that 37.7% of the students experienced ethical problems,24.6% experienced ethical dilemmas in clinical practices.The students stated that the ethical principles most frequently violated in the problems they experienced were;benefit, non-maleficence, equality, and privacy, respectively.It was stated that the ethical values violated when they experienced ethical problems were mostly human dignity and honesty. When they experienced ethical problems, 24.9% of the students stated that they made ethical decisions, 8.9% stated that they could not make ethical decisions, and 8.3% stated that they had no idea. The total score of the Scale of Ethical Problems experienced by the students in clinical education was found to be 146.72±39.21. A significant difference was found between the ethical problem scores according to the students' gender, the number of clinical practice, and the status of experiencing ethical problems in clinical practice (p<0.05).